1975
DOI: 10.1002/app.1975.070190917
|View full text |Cite
|
Sign up to set email alerts
|

The fracture of epoxy- and elastomer-modified epoxy polymers in bulk and as adhesives

Abstract: SynopsisThe fracture behavior of a piperidinemisphenol A diglycidyl ether (A) resin has been determined in bulk a q l as an adhesive using the linear elastic fracture methods developed by Mostovoy. The effect of adding carboxy-terminated butadiene-acrylonitrile (CTBN) elastomer to resin A was investigated. The opening-mode fracture energy (91~) of resin A was 120 to 150 J/m2, and largely attributable to plastic deformation. Fractographic evidence was obtained for plastic flow a t the crack tip during crack ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
168
1
6

Year Published

1985
1985
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(189 citation statements)
references
References 0 publications
10
168
1
6
Order By: Relevance
“…Mostovoy et al [5] investigated the effects of adhesive joint geometry on the toughness of commercial toughened epoxy adhesives with aluminium adherends and found that an increase in bond gap thickness resulted in an increase in toughness. Bascom et al [1] also investigated the behaviour of rubber--modified epoxy resin using the tapered double--cantilever beam (TDCB) configuration and found that the fracture energy is maximized when the bond thickness equals the diameter of the plastic zone formed ahead of the crack tip.…”
Section: Introductionmentioning
confidence: 99%
“…Mostovoy et al [5] investigated the effects of adhesive joint geometry on the toughness of commercial toughened epoxy adhesives with aluminium adherends and found that an increase in bond gap thickness resulted in an increase in toughness. Bascom et al [1] also investigated the behaviour of rubber--modified epoxy resin using the tapered double--cantilever beam (TDCB) configuration and found that the fracture energy is maximized when the bond thickness equals the diameter of the plastic zone formed ahead of the crack tip.…”
Section: Introductionmentioning
confidence: 99%
“…In Regime III, for ℎ ℎ >0.45 mm, the adhesive fracture energy decreases somewhat at first and then reaches a plateau value with a magnitude significantly larger than the lowest value which is exhibited for very thin adhesive layers. In previous experimental studies, Regime I has been observed by Chai (1986Chai ( , 1988, and Regimes II and III by Bascom et al (1975), Kinloch and Shaw (1981) and Chai (1986). Fig.…”
Section: Effect Of the Thickness Of The Adhesive Layer Hadhmentioning
confidence: 68%
“…As might be expected, experimental studies have been carried out with a view to ascertain these effects. In particular, several researchers (Bascom et al, 1975;Chai, 1986Chai, , 1988Kinloch and Shaw, 1981) have shown that the adhesive fracture energy, , is a nonlinear function of the thickness of the adhesive layer. This effect was qualitatively explained by Kinloch and Shaw (1981) from the magnitude of the plastic dissipation in the adhesive layer being dependent upon the degree of constraint, which was supported by some experimental evidence (Hunston et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Azari, Papimi and Spelt [27] reported in 2009 that certain researchers had found that increasing t a caused an increase in joint strength [28,29], some observed a strength decrease [5,30,31] and some no significant change at all [31,32]. A second 2009 investigation by Grant et al [26] with joints subjected to four-point bending concluded that the strength was "independent of the adhesive thickness", an "increase in adhesive thickness causes the joint overlap section to be stiffer" and that, for tension loading the strength increases with increased t a .…”
Section: Page 19mentioning
confidence: 99%